Anthocyanins and musculoskeletal diseases: mechanisms and therapeutic potential - Lv, Xing; Zhao, Xiao-peng; Li, Wen-cong; Xing, Nai-fei; Zong, Ke-qiang; Zhai, Yi; Yang, Sheng-lei; Zhang, Ji-yao; Liu, Xia (Frontiers in Nutrition, 2025)
BackgroundMusculoskeletal diseases (MSDs) are a common group of conditions involving bones, muscles, cartilage, ligaments, and nerves, which significantly impact patients’ quality of life and ability to participate in society. Anthocyanins (ACNs), as phytochemicals, possess various pharmacological and biological activities, including anti-apoptotic, antioxidant, anti-inflammatory, and immunosuppressive properties. In recent years, ACNs have shown remarkable potential in improving MSDs. This review article aims to recapitulate the therapeutic potential of ACNs and its mechanism of action in treating MSDs.MethodsExtensive literature was searched and reviewed through online electronic databases (PubMed, Embase, and Web of Science), focusing on analysing the specific roles and molecular mechanisms of ACNs in in vivo and in vitro studies.ResultsACNs exert protective effects on MSDs by targeting multiple key signaling pathways, including mitogen-activated protein kinase (MAPK), nuclear factor-kappaB (NF-κB), Wingless-related integration site (Wnt)/β-catenin, phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt), adenosyl monophosphate-dependent protein kinase (AMPK), receptor activator of nuclear factor-kappaΒ/receptor activator of nuclear factor-kappaB ligand/osteoprotegerin (RANK/RANKL/OPG) and oxidative stress signaling. In addition, ACNs exhibited anti-inflammatory, anti-apoptotic, and immunosuppressive properties. This article reviews the mechanisms and potential therapeutic applications of ACNs in the prevention and alleviation of MSDs, providing valuable reference points for further research and development of ACNs.ConclusionACNs improve the prevention of MSDs through multiple actions such as antioxidant, anti-inflammatory, immunomodulatory and bone metabolism homeostasis regulation. However, results from in vitro and in vivo studies still need to be further validated by human clinical trials.